Microbial Biotechnologies for Salt Tolerance in Alfalfa: Agro-Nutritional Comparison Between Local and Imported Varieties - Raja Ben-Laouane; Mohamed Ait-El-Mokhtar; Mohamed Anli; Abderrahim Boutasknit; Khalid Oufdou; Said Wahbi; Abdelilah Meddich (Nitrogen, 2025)
Increasing soil salinity is threatening agricultural productivity which implies the development of new sustainable strategies to deal with this challenge. The main objective here is to assess the potential for improving the tolerance of alfalfa to salinity by combining inoculations with rhizobia and AMF. However, the distinguishing feature of this study is the comparison of two alfalfa varieties’ microbial response to salinity. The greenhouse trial was conducted on an Australian variety Siriver and an indigenous Demnate population, which were inoculated with Rhizoglomus irregulare and/or native AMF, and/or a RhOL1 rhizobial strain. The RhOL1 strain was selected from nine rhizobia tested for their plant growth promoting rhizobacteria (PGPR) activities. In addition to its ability to tolerate high salinity levels (769 mM) and solubilize insoluble phosphate as well as potassium, it can also synthesize auxins such as IAA. The application of these biofertilizers was carried out in the absence and the presence of the saline stress (0 and 120 mM NaCl). The double inoculations of native AMF and RhOL1 significantly improve the shoot and root dry biomass, plant elongation, number of formed leaves, and mineral nutrition, as well as the number of nodules and the rate of mycorrhizal root colonization. The synergistic effects between the native AMF and RhOL1 strain have been demonstrated in this study. However, the behavior of alfalfa genotypes towards microbial inoculation was significantly different. The ability to react to the double indigenous RhOL1 + AMF inoculation is more important in the Siriver than in the Demnate population. Thus, the possibility of formulating biofertilizers is based on the AMF–rhizobia–hote tripartite combination for alfalfa production in saline areas.